Bacterial Cellulose-Hydroxyapatite Nanocomposites for Bone Regeneration - S. Saska; H. S. Barud; A. M. M. Gaspar; R. Marchetto; S. J. L. Ribeiro; Y. Messaddeq (International Journal of Biomaterials)
The aim of this study was to develop and to evaluate the biological properties of bacterial cellulose-hydroxyapatite (BC-HA) nanocomposite membranes for bone regeneration. Nanocomposites were prepared from bacterial cellulose membranes sequentially incubated in solutions of CaCl2 followed by Na2HPO4. BC-HA membranes were evaluated in noncritical bone defects in rat tibiae at 1, 4, and 16 weeks. Thermogravimetric analyses showed that the amount of the mineral phase was 40%–50% of the total weight. Spectroscopy, electronic microscopy/energy dispersive X-ray analyses, and X-ray diffraction showed formation of HA crystals on BC nanofibres. Low crystallinity HA crystals presented Ca/P a molar ratio of 1.5 (calcium-deficient HA), similar to physiological bone. Fourier transformed infrared spectroscopy analysis showed bands assigned to phosphate and carbonate ions. In vivo tests showed no inflammatory reaction after 1 week. After 4 weeks, defects were observed to be completely filled in by new bone tissue. The BC-HA membranes were effective for bone regeneration.